ECO-INTERRELIGIOUS DIALOGUE IN DAILY RELIGIOUS PRAXIS: A PERSPECTIVE OF ORGANIC FARMERS IN CENTRAL JAVA - Chlaodhius Budhianto; Rinda Fauzian; Matroni; Nurfah; Munadzir (Harmoni, 2026)
This research aims to explore the dynamics of eco-interreligious dialogue through the approach of everyday religion, particularly in the context of organic farming. This research examines how organic farmers in Central Java integrate religious values into their ecological practices, how they relate to farmers of different faiths, how they manage the environment, and how they interact with others. This research approach uses ethnography, with data collected through field research including participatory observation, interviews, and documentation of Muslim and Christian farmers, focusing on organic farmers in Batur Village, Getasan, Central Java. The research results show that organic farming is a form of religious practice in which concern for the environment is closely linked to religious commitment. The farmers' views on land as sacred and their moral responsibility toward nature are strongly influenced by their religious teachings, though these are understood and practiced in different ways. Additionally, this research also highlights the role of eco-interreligious dialogue in building cooperation among farmers from different religious backgrounds. Although tensions sometimes arise, this dialogue facilitates mutual understanding and shared responsibility in religious practices and environmental preservation. However, this research also identifies contradictions in religious narratives that hinder the achievement of a consistent theological stance toward interfaith and ecology. This research suggests that eco-interreligious dialogue should develop not only on doctrinal agreements but more on real religious experiences through the harmony of religious practices, especially in maintaining ecological sustainability. Through this approach, this research contributes to a broader understanding of how religion and ecology interact in daily life and provides insights into future religious harmony and interfaith environmental cooperation.  Abstrak Penelitian ini bertujuan mengeksplorasi dinamika dialog antaragama yang berwawasan lingkungan melalui pendekatan agama sehari-hari, khususnya dalam konteks pertanian organik.  Penelitian ini meneliti bagaimana petani organik di Jawa Tengah mengintegrasikan nilai-nilai agama ke dalam praktik ekologi mereka, bagaimana mereka berhubungan dengan petani dari berbagai keyakinan, bagaimana mereka mengelola lingkungan, dan bagaimana mereka berinteraksi dengan orang lain.  Pendekatan penelitian ini menggunakan etnografi, dengan data yang dikumpulkan melalui penelitian lapangan termasuk observasi partisipatif, wawancara, dan dokumentasi petani Muslim dan Kristen, yang berfokus pada petani organik di Desa Batur, Getasan, Jawa Tengah.  Hasil penelitian menunjukkan bahwa pertanian organik adalah bentuk praktik keagamaan di mana kepedulian terhadap lingkungan sangat terkait dengan komitmen religius.  Pandangan para petani tentang tanah sebagai suci dan tanggung jawab moral mereka terhadap alam sangat dipengaruhi oleh ajaran agama mereka, meskipun ini dipahami dan dipraktikkan dengan cara yang berbeda.  Selain itu, penelitian ini juga menyoroti peran dialog antaragama ekologis dalam membangun kerjasama di antara petani dari latar belakang agama yang berbeda.  Meskipun kadang-kadang muncul ketegangan, dialog ini memfasilitasi saling pengertian dan tanggung jawab bersama dalam praktik keagamaan dan pelestarian lingkungan.  Namun, penelitian ini juga mengidentifikasi kontradiksi dalam narasi-narasi keagamaan yang menghambat pencapaian sikap teologis yang konsisten terhadap antaragama dan ekologi.  Penelitian ini menyarankan bahwa dialog antaragama yang berfokus pada ekologi harus berkembang tidak hanya pada kesepakatan doktrinal tetapi lebih pada pengalaman religius yang nyata melalui harmoni praktik keagamaan, terutama dalam menjaga keberlanjutan ekologi.  Melalui pendekatan ini, penelitian ini berkontribusi pada pemahaman yang lebih luas tentang bagaimana agama dan ekologi berinteraksi dalam kehidupan sehari-hari dan memberikan wawasan tentang harmoni agama di masa depan serta kerja sama lingkungan antaragama.